HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DAN KELUARGA DI RAWAT INAP RS LNG BADAK BONTANG - Dewi Kurnia Sari; Supriadi; Ratanto (Jurnal Cakrawala Ilmiah, 2024)
Introduction: Caring is a basic human need and an important component of the nursing profession. Effective caring promotes healing, health, individual and family growth, a sense of wholeness and inner peace that transcends illness, trauma and life changes. Care is one of the benchmarks for health service users. The nurse’s behavior that must be implemented is to be able to provide a sense of comfort, attention, caring affection, encouragement, empathy and interest, love, trust, protection, presence, support, giving touch, and being ready to help, and visit patients. This study aims to determine the relationship between nurses’ caring behavior and the level of patient and family satisfaction in inpatient care at the Badak Bontang LNG Hospital, East Kalimantan. Method: The research design used in this research is a descriptive correlation research design with a cross sectional analytical design. With a total of 100 respondents using a purposive sampling technique. Data analysis used to analyze the relationship between caring nurses and level of satisfaction uses Rank Spearman Analysis where both variables are on an ordinal scale. Results: The test results showed that the majority of nurses had provided sufficient caring and 75% of patients were very satisfied with the services provided. From the test results obtained, p = 0.000, meaning p < 0.05, this shows that there is a significant relationship between caring nurses and the level of patient and family satisfaction in the Inpatient Hospital LNG Bontang, East Kalimantan. Conclusion: There is a relationship between caring nurses and the level of patient and family satisfaction in the Inpatient Hospital LNG Badak Bontang, East Kalimantan.